ChemInform Abstract: One‐Pot Synthesis of Tryptanthrin by the Dakin Oxidation of Indole‐3‐carbaldehyde. Issue 10 (March 2015) - Abe, Takumi; Itoh, Tomoki; Choshi, Tominari; Hibino, Satoshi; Ishikura, Minoru
Abstract The alkaloid tryptanthrin (IIa) is further converted into the natural products phaitanthrin A (IXa), phaitanthrin B (IXb), and cruciferane (X).